Comparative study between biofeedback pelvic floor training with and without transabdominal electrucal nerve stimulation in consitpation in children with spina bifida - Mervat Sheta Elsawy; Hadir Hassouna; Ahmed Elrouby (Alexandria Journal of Medicine)
Introduction Constipationin pediatric patients having Spinabifida (SB) is a common problem which does not only play a major health problem but also adds an economic and emotional problem to such patients and their families. Biofeedback and trans-abdominal electrical nerve stimulation are new modalities of treatment for this condition; however there actual efficacy in such condition was not clearly studied.Aim of the Work Comparison between the efficacy of biofeedback alone and in association with trans-abdominal electrical nerve stimulation in the management of constipation in pediatric patients with SB bifida.Material and Methods Prospective randomized controlled study included 40 pediatric patients with SB bifida complaining of constipation ranging between six and 14 years old. These patients were divided randomly into two groups: the 1st group (Group A) was managed by biofeedback alone and the 2nd group (Group B) was managed by biofeedback in association with trans-abdominal electrical nerve stimulation. Both groups were compared before and after the application of the two management planes by using the constipation score as a subjective assessment tool and by the mean of maximum anal pressure during straining as an objective tool.Results Patients who received biofeedback in combination with trans-abdominal electrical nerve stimulation showed significant improvement in the constipation scoreas well as in the mean of maximum anal pressure during straining in comparison to those who received biofeedback only (Mann Whitney test, U = 116.0, p = 0.023*).Conclusion The addition of trans-abdominal electrical nerve stimulation to biofeedback in case of constipation in pediatric patients with SB bifida is highly effective with better outcome as compared with the application of biofeedback alone.